Nadoofa station / Hendi Kurniadi ... [et al.] - Kurniadi, Hendi; Siregar, Rizki Agung Syah Putra; Haydar, Anggita; Nengsih, Desty Widia; Kinanthi, Dita Nur (2020)
Covid-19 has not been getting better. The amount of covid-19 case increases each day not only in Indonesia but also globally. The increase of the case causes the health protocol is strictly being implemented in public space. Yogyakarta which is known as a cultural and tourism city becomes one of region that needs to do a preventive effort to overcome covid-19. The obligation to wash the hands as often as possible cause a buildup grey water (waste of the handsoap) and the decrease of clean water availability. The condition of the washing hands facilities are unpretentious and inefficient. The objective of this innovation design is to design an efficient and green solution of washing hands facility that includes a recycle system of the grey water and responses to new normal. The design method uses literature review that relates to covid-19, waste liquid, and the sink/wash basin system. Besides research that makes the closure of issue from the aspect of behavioural, ergonomic, ecological, economical, and healthy closures. The Innovation and novelty of our design is a sink/wash basin design that uses recycle and re-use water with a complete of grey water's recycle system.